Livelihoods, growth, and links to market towns in 15 Ethiopian villages - Dercon, Stefan; Hoddinott, John F. (International Food Policy Research Institute, 2005)
This paper uses longitudinal data from 15 villages in rural Ethiopia to explore the nature and consequences of these links. It addresses the following questions: (1) What are the links between rural households and local urban centers? (2) Does better access to local market towns affect household economic behavior? and (3) Does better access to local market towns make households better off? ...In our results, market towns and cities are an important source of demand for products produced in rural areas, and rural residents are a source of demand for goods sold in urban areas. Improving the presence of roads, their quality, and improved transport are important factors that willfurther bind these spaces together and improve rural welfare market towns.